PENERAPAN KOMUNIKASI PERSUASIF DI APLIKASI SHOPEE LIVE TERHADAP MINAT BELI PRODUK - Nurul Saniah; Dedek Adi Syaputra (Pojok Publisher, 2024)
The Shopee application is an online market platform that provides a means for sellers (business owners) to interact with buyers. Or a means to buy some products that consumers want. Shopee products cover various categories, such as electronics, kitchen equipment, and fashion. In achieving its target, Shopee uses a live feature on the Shopee application called Shopee Live. Shopee Live is one of the supporting features in the Shopee application that aims to promote products sold with various attractive discounts, usually these discounts are only available during live. Which sometimes allows application users to watch and follow the Shopee Live. In promoting their products live, sellers must be able to influence consumers or viewers who watch the live or even sellers must be able to convince consumers to buy products that are promoted live. Therefore, sellers must be able to understand persuasive communication techniques to invite consumers to be interested in the products they sell. Persuasive communication is used to influence the beliefs, values, and attitudes of consumers. Many persuasive communication theories are closely related to the marketing of a product or service. The influence of persuasive communication is very large for products sold in the promotion process and sellers must have the ability to convince consumers when promotions on Shopee Live take place.